The Importance of Infrastructural Facilities in The University - J. Krishnaiah; Syeda Akhtar Begum; Y. Madhuri; M. Kamraju (Universitas Pendidikan Indonesia (UPI), 2024)
Infrastructure development is a crucial factor that must be taken into consideration in both schools and institutions of higher education. Numerous components make up the broad concept of infrastructure. These consist of things like playgrounds, libraries, labs, computer centers, technology, machinery, tools, and other things. To upgrade the infrastructure, the educational institutions' members must invest money. Infrastructure improvements will enable people to perform their jobs properly and advance educational institutions by enabling people to carry out their job tasks. The staff members of educational institutions must make sure that they continuously upgrade the infrastructure available to them. The main objective of the paper is to study infrastructural facilities in schools. For the research data has been collected with the help of a questionnaire through personal visits to the schools. The outcome of the results will be helpful to the stakeholders and government.